FRI0604-HPR IS STRESS A TRIGGER FOR THE DEVELOPMENT OF SYSTEMIC LUPUS ERYTHEMATOSUS?. (2nd June 2020) - Soria Curi, Y.; Barbaglia, A. L.; Gonzalez Lucero, L.; Bertolaccini, M. C.; Sueldo, H. R.; Mazza, S. M.; Leguizamón, M. L.; Espasa, G. V.; Pera, M.; Bellomio, V. I.
Abstract : Background: Systemic Lupus Erythematosus (SLE) implies multifactorial psychological stress. Although stress has been spreaded as a "trigger" for the onset or flare of connective tissue diseases, there is controversial evidence of the association between stress and the diagnosis of SLE. Objectives: To assess the frequency of stressors and vital events in patients with SLE and their relationship with the diagnosis. Methods: A descriptive cross-sectional study was conducted. It were included patients over 18 years old with SLE diagnosis (ACR/SLICC criteria), attended in the Rheumatology Unit between May and August 2019; and 101 patients without any autoimmune disease. Demographic and disease-related variables were studied. The Holmes and Rahe Vital Events scale (43 questions) was used to evaluate vital events and measure the magnitude of stress that a person has experienced for a while and predict the onset of SLE. The sum of the scores indicates the magnitude of vital stress experienced by a person and the predisposition to acquire a disease. It was classified as: <150: small risk of illness due to stress; 150-299: moderate risk; and ≥ 300: high risk. Results: 94 patients with SLE were included, of which 94% were women. The mean age was 36.3 ± 10.3 years. 41.9% of the cases had a family history of rheumatic disease and 31.2% of them were unemployed. During the year before the diagnosis of SLE, 48.4% of the patients suffered a stressful situation, the most frequent cause was the death of a close family member (44.1%). Patients with SLE presented significantly higher stress scores than the healthy group (140 ± 27 vs. 45.1 ± 43, p=0.0001); 54.8% of patients with SLE had a score <150; 23.65% between 150-299; and 10.75% ≥ 300. The number of patients with SLE was higher in the moderate and high risk categories (>150) than the healthy group (34% vs. 2%, p=0.0001). When studying the Holmes and Rahe scale factors individually, patients with SLE had a higher frequency of situations related to: death of the couple (p=0.029), death of a close relative (p=0.0001), injury or personal illness (p=0.006), change in living conditions (p=0.0001) and poor relationship with the couple (p=0.017). Conclusion: Patients with SLE presented high frequency of stressful situations before diagnosis (48.4%), and higher scores compared to the healthy group. The death of a close family member was the most frequent stressful event. Disclosure of Interests: None declared